Estudio geológico - geotécnico previo a la construcción del Puerto Seco Comercial, sector Plateado, cantón y provincia de Loja. - Jiménez Saritama, Stalin Moises (2018)
The present research project developed in “Plateado” neighborhood in the western of Loja City and denominated “GEOLOGICAL- GEOTHECNICAL STUDY PREVIOUS TO THE CONSTRUCTION OF THE PUERTO SECO COMERCIAL, IN THE PLATEADO PLACE, CANTON AND PROVINCE OF LOJA, is focused on raising awareness the real conditions of the land from the geological and geotechnical point of view before starting with the initial phase of construction. For this, field work was carried out, such as the detailed topographic exploration, raising an area of 28.9 hectares, of which 7.8 hectares correspond to the polygon of construction of the Puerto Seco Comercial. The research area is geologically composed of sedimentary materials from the “La Banda” formations (shales, sandstones) and from Belén (clays, sandstones and conglomerates), this information was obtained based on the description of outcrops and pits. As units geomorphological defined are; soft relief of hill (36.8%), high terrace (25.3%), middle slope relief (23.4%), and front slope (14.5%). Through the application of direct methods focused on determining the physico-mechanical characteristics of soil, standard Penetration test (SPT) and a diamond drilling tests executed. With the application of indirect methods, vertical electrical sounding allowed to obtain a range of values of apparent resistivity, ranging from 1.8 Ω.m that correspond to saturated muds, to 15.2 Ω.m in the case of sand clays. With the standard penetration tests, laboratory work and according to the soil classification (SUCS), it was determined that in depth up to 8m, there are clay soils (CH1), sand soils (CH2), inorganic muds (MH1), clayey gravel (GC), silty gravel (GM), clay sands (SC), thus being able to vary its volume and with this to present alterations in surface; of the diamond drilling (15m), it was evidenced that the type of clay-sandy material continues in depth, highlighting that the water level was found at 2m.